Coupled numerical and experimental analyses of load transfer mechanisms in granular-reinforced platform overlying cavities. Issue 5 (October 2019) - Chalak, Caroline; Briançon, Laurent; Villard, Pascal
Abstract: A numerical model based on Finite Element Method (FEM) - Discrete Element Method (DEM) coupling is used to reproduce well controlled laboratory experiments that simulate circular cavity openings under granular embankments reinforced by a geotextile. The numerical deflection of the geotextile, the surface settlement and the soil expansion factor were investigated for various embankment heights, diameter ratios, cavity-opening modes, soil properties, and geotextile stiffnesses, and then compared to the results of laboratory tests. The load transfer mechanisms were also investigated. Good agreement between numerical and experimental results is shown, thus demonstrating the relevance of the numerical model. Complementary to the experiments, a numerical sensitivity analysis, that allows highlighting the influence of the main parameters and improving experimental observation, was also performed.